Spontaneous nystagmus with an upbeat component: Central or peripheral vestibular disorders? - Ling, Xia; Wu, Yue-Xia; Feng, Yu-Fei; Zhao, Tong-Tong; Zhao, Gui-Ping; Kim, Ji-Soo; Yang, Xu; Wang, Zhao-Xia (Frontiers in Neurology, 2023)
Objective To determine the topical diagnosis and etiologies of spontaneous nystagmus (SN) with an upbeat component. Methods We retrospectively recruited 43 patients with SN with an upbeat component at a university hospital in China from 2020 to 2022. SN with an upbeat component was divided into pure upbeat nystagmus (UBN), SN with a predominant upbeat component, and SN with a non-predominant upbeat component. We analyzed their clinical and neurotologic findings and the final diagnosis. Results Fourteen (32.6%) of them showed pure UBN, while 29 (67.4%) exhibited SN mixed with an upbeat component, mixed upbeat-horizontal in 15, mixed upbeat-horizontal-torsional in 13, and upbeat-torsional in the remaining one. Pure UBN and SN with a predominant upbeat component were more common in central than in peripheral vestibular disorders [16 (80.0%) vs. 0 (0%), Chi-Square test, p < 0.001]. Central vestibular disorders were diagnosed in 20 (46.5%) patients, peripheral in 14 (32.6%), and undetermined in nine (20.9%) patients. The underlying causes mainly included acute unilateral peripheral vestibulopathy (n = 11), posterior circulation infarction (n = 9), benign recurrent vertigo (n = 4), vestibular migraine (VM, n = 3), and VM of childhood (n = 2). Conclusion SN with an upbeat component can be seen in both central and peripheral vestibular disorders. Pure UBN was a characteristic sign of central vestibular dysfunction. Central vestibular disorders should be highly suspected when patients show pure UBN or SN with a predominant upbeat component.